Exopolysaccharide Produced by Lactiplantibacillus plantarum-12 Alleviates Intestinal Inflammation and Colon Cancer Symptoms by Modulating the Gut Microbiome and Metabolites of C57BL/6 Mice Treated by Azoxymethane/Dextran Sulfate Sodium Salt - Fenglian Ma; Yinglong Song; Mengying Sun; Arong Wang; Shujuan Jiang; Guangqing Mu; Yanfeng Tuo (Foods, 2021)
Exopolysaccharide produced by Lactiplantibacillus plantarum-12 (LPEPS) exhibited the anti-proliferating effect on human colon cancer cell line HT-29 in vitro. The purpose of the study was to determine the alleviating effects of LPEPS on colon cancer development of the C57BL/6 mice treated by azoxymethane/dextran sulfate sodium salt (AOM/DSS). The C57BL/6 mice treated by AOM/DSS were orally administered LPEPS daily for 85 days. The results showed that LPEPS oral administration enhanced colon tight-junction protein expression and ameliorated colon shortening and tumor burden of the AOM/DSS treated mice. Furthermore, LPEPS oral administration significantly reduced pro-inflammatory factors TNF-α, IL-8, and IL-1β levels and increased anti-inflammatory factor IL-10 level in the serum of the AOM/DSS-treated mice. LPEPS oral administration reversed the alterations of gut flora in AOM/DSS-treated mice, as evidenced by the increasing of the abundance of Bacteroidetes, Bacteroidetes/Firmicutes ratio, Muribaculaceae, Burkholderiaceae, and norank_o__Rhodospirillales and the decreasing of the abundance of Firmicutes, Desulfovibrionaceae, Erysipelotrichaceae, and Helicobacteraceae. The fecal metabolites of the AOM/DSS-treated mice were altered by LPEPS oral administration, involving lipid metabolism and amino acid metabolism. Together, these results suggested that LPEPS oral administration alleviated AOM/DSS-induced colon cancer symptoms of the C57BL/6 mice by modulating gut microbiota and metabolites, enhancing intestine barrier, inhibiting NF-κB pathway, and activating caspase cascade.